2007
DOI: 10.1037/0022-0663.99.2.326
|View full text |Cite
|
Sign up to set email alerts
|

The role of lexical analogies in beginning reading: Insights from children's self-reports.

Abstract: The research addresses the role of lexical analogies in early reading by examining variation in children's self-reported strategy choices in the context of a traditional clue-word reading task. Sixty 5-to 6-year-old beginning readers were given a nonword version of a traditional clue-word reading analogy task, and changes in strategies were examined using measures of immediately retrospective verbal reports. The findings revealed that the children's performance was accompanied by their use of a wide repertoire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…Nonetheless, while some researchers argue that such strategies are available to young children in the very early stages of learning to read (Farrington-Flint & Wood, 2007;Goswami, 1988Goswami, , 1990aGoswami, , 1990bGoswami, , 1993, others have documented how children need a well-developed sight vocabulary as a basis for making analogies between familiar and unfamiliar words (Ehri, 1998;Ehri & Robbins, 1992). It is important to note that the former claims are often based on experimental studies that specifically train children to recognise words based on similar rime units using clue-word prompts.…”
Section: Variability In Children's Early Reading Strategiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Nonetheless, while some researchers argue that such strategies are available to young children in the very early stages of learning to read (Farrington-Flint & Wood, 2007;Goswami, 1988Goswami, , 1990aGoswami, , 1990bGoswami, , 1993, others have documented how children need a well-developed sight vocabulary as a basis for making analogies between familiar and unfamiliar words (Ehri, 1998;Ehri & Robbins, 1992). It is important to note that the former claims are often based on experimental studies that specifically train children to recognise words based on similar rime units using clue-word prompts.…”
Section: Variability In Children's Early Reading Strategiesmentioning
confidence: 96%
“…Ehri, 1998;Treiman, 1993;Treiman, Cassar, & Zukowski, 1994). Reliance solely on phonological strategies can therefore often lead to relatively low levels of word reading accuracy (Farrington-Flint et al, 2008;Farrington-Flint & Wood, 2007;Rittle-Johnson & Siegler, 1999).…”
Section: Variability In Children's Early Reading Strategiesmentioning
confidence: 97%
“…Although a person is aware of the orthographic rules and phonological features of their language, a correct spelling or articulation of a specific word is not guaranteed (Rittle-johnson & Siegler, 1999). Nevertheless, recent studies have shown that the assumptions of the Overlapping Waves Model can be transferred to reading and spelling in the English language Farrington-Flint et al, 2009;Farrington-Flint & Wood, 2007;Siegler, 1988). It is important to emphasize that in these studies, not only indicators were found for variability, adaptive choice, and gradual change in children's strategy use, but also a direct retrieval of facts for reading and writing skills.…”
Section: Strategies In Reading and Arithmeticmentioning
confidence: 96%
“…Especially during the acquisition of new skills within an unknown domain, several competing and/or alternative and complement strategies are present in a person's attempt to master a specific task. Variability in children's strategy use is characteristic for skills in academic development: arithmetic (Canobi, 2004;Canobi, Reeve, & Pattison, 2003;Lemaire & Siegler, 1995;Siegler & Shrager,1984), reading (Farrington-Flint, Coyne, Stiller, & Heath, 2008;Farrington-Flint & Wood, 2007;Jorm & Share, 1983) and spelling Kwong & Varnhagen, 2005;Rittle-johnson & Siegler, 1999). In all these domains children rarely apply only one approach to solve a task: in fact, they use several different approaches to attaining a certain goal.…”
Section: Variabilitymentioning
confidence: 97%
See 1 more Smart Citation